2022
DOI: 10.1371/journal.pmed.1004015
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with SARS-CoV-2 infection in a multiethnic cohort of United Kingdom healthcare workers (UK-REACH): A cross-sectional analysis

Abstract: Background Healthcare workers (HCWs), particularly those from ethnic minority groups, have been shown to be at disproportionately higher risk of infection with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) compared to the general population. However, there is insufficient evidence on how demographic and occupational factors influence infection risk among ethnic minority HCWs. Methods and findings We conducted a cross-sectional analysis using data from the baseline questionnaire of the United K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 33 publications
4
55
0
Order By: Relevance
“…These findings may be due to a lower perceived risk of infection or severe illness due to younger age or having previously suffered minor symptoms from COVID-19 (although, in our study, we did not find an association between perceived risk of hospitalisation with COVID-19 and hesitancy). Emerging evidence suggests that re-infection risk increases with time, especially with omicron and its subvariants [ 22 , 23 ]. Whilst reinfection does not necessarily result in severe disease, reinfected HCWs may emit large quantities of virus for limited periods of time [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings may be due to a lower perceived risk of infection or severe illness due to younger age or having previously suffered minor symptoms from COVID-19 (although, in our study, we did not find an association between perceived risk of hospitalisation with COVID-19 and hesitancy). Emerging evidence suggests that re-infection risk increases with time, especially with omicron and its subvariants [ 22 , 23 ]. Whilst reinfection does not necessarily result in severe disease, reinfected HCWs may emit large quantities of virus for limited periods of time [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment is described in detail in the study protocol [ 19 ] and in previous publications [ 20 22 ]. In brief, participating UK healthcare regulators (for a list of regulators, see Additional file 1 : Supplementary text) sent emails to their registrants informing them of the study.…”
Section: Methodsmentioning
confidence: 99%
“…29 Pre-reinfection LV-N and PV-N titres were significantly lower in cases than controls, supporting the mounting evidence that neutralising activity is critical for protection against SARS-CoV-2 infection. [11][12][13]30 It is know that titres and longevity of nAb are directly associated with clinical presentation of the primary COVID-19 episode, given asymptomatic SARS-CoV-2 infections induce lower levels and a more rapid decline of nAb titres over time when compared to moderate or severe infection. [31][32][33] However, we were unable to investigate this here as both groups in our study overwhelmingly reported mild or asymptomatic primary infections and none were hospitalised.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a suitable antibody response after first infection, influenced by epidemiological factors such as severity of infection and immunosuppression, and decreasing neutralising antibody (nAb) titres over time were associated with SARS-CoV-2 reinfection. [10][11][12][13] nAb titres to specific variants may be more relevant for sterilising immunity than total IgG or binding antibody levels, thus a more accurate correlate of protection against infection. 14,15 When comparing individuals who experienced reinfection and those after recover from primary infection (convalescent), no difference in antibody levels within weeks after reinfection were found.…”
Section: Introductionmentioning
confidence: 99%
“…The augmented burden of COVID-2019 infection on HCWs and their families, specifically those from ethnic minority groups, has been reported, raising concerns about the protection of those at highest risk 1–3. Research on the interdependency of ethnicity with other essential risk factors, such as occupation has been scant 1 3 4.…”
Section: Contextmentioning
confidence: 99%